Gametogenesis and reproductive dynamics of scinax acuminatus (Anura: Hylidae): Morphological, histological and immunohistochemical analysis - Olea, Gabriela Beatriz (2021)
To characterize the reproductive biology of Scinax acuminatus and contribute to the natural history of this species, the morphology of the reproductive system of males and females was analyzed at anatomical, histological and immunohistochemical levels. The individuals were collected fortnightly between August and December (2016) and January to December (2018). The anatomy of the reproductive system was analyzed in a stereoscopic microscope, and histological preparations staining with hematoxylin-eosin and Masson’s trichromic, PAS and Coomassie Blue was performed as well. To characterize the meiotic-active cells in the testes, immunostaining with the PCNA proliferation protein was performed. There were found females with ovaries with oocytes in different stages of maturity and post-ovulatory females. Males presented continuous spermatogenesis, which could be confirmed by the immunostaining of PCNA in spermatogonia during the cycle. The results of this work serve as a basis for the characterization of the reproductive cycle in S. acuminatus and provide background information on the analysis of spermatogenic activity by IHQ from the study of the immunodetection of the PCNA cell proliferation protein. Future studies will focus on the evaluation of cell death processes during the reproductive cycle in the studied species to compare with those obtained in terms of cell proliferation.